On the CUSP: the politics and prospects of scaling social norms change programming. Issue 2 (31st May 2019) - Goldmann, Leah; Lundgren, Rebecka; Welbourn, Alice; Gillespie, Diane; Bajenja, Ellen; Muvhango, Lufuno; Michau, Lori
Abstract: In the past decades, donors and development actors have been increasingly mindful of the evidence to support long-term, dynamic social norms change. This paper draws lessons and implications on scaling social norms change initiatives for gender equality to prevent violence against women and girls (VAWG) and improve sexual and reproductive health and rights (SRHR), from the Community for Understanding Scale Up (CUSP). CUSP is a group of nine organisations working across four regions with robust experience in developing evidence-based social norms change methodologies and supporting their scale-up across various regions and contexts. More specifically, the paper elicits learning from methodologies and experiences from five CUSP members – GREAT, IMAGE, SASA!, Stepping Stones, and Tostan. The discussion raises political questions around the current donor landscape including those positioned to assume leadership to take such methodologies to scale, and the current evaluation paradigm to measure social norms change at scale. CUSP makes the following recommendations for donors and implementers to scale social norms initiatives effectively and ethically: invest in longer-term programming, ensure fidelity to values of the original programmes, fund women's rights organisations, prioritise accountability to their communities and demands, critically examine the government and marketplace's role in scale, and rethink evaluation approaches to produce evidence that guides scale-up processes and fully represents the voices of activists and communities from the Global South.